2016
DOI: 10.1039/c6cc04470k
|View full text |Cite
|
Sign up to set email alerts
|

Chiral recognition at self-assembled multivalent (SAMul) nanoscale interfaces – enantioselectivity in polyanion binding

Abstract: Self-assembled multivalent (SAMul) ligands based on palmitic acid functionalised with cationic l/d-lysine bind polyanionic heparin or DNA with no chiral preference. Inserting a glycine spacer unit switches on chiral discrimination - a rare example of controlled chiral recognition at a SAMul nanoscale interface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 37 publications
2
22
0
Order By: Relevance
“…We have reported that a chiral SAMul lysine ligand array can control polyanion binding . Interestingly, however, when using lysine ligands, chiral recognition of heparin does not always occur—Wang and Rabenstein reported that there was no impact of chirality in their peptide heparin binders, whilst we found that the precise structure of the self‐assembling system determined whether chiral recognition was achieved . In this new study, we wanted to gain a more detailed understanding of the chiral preferences of both heparin and DNA, and unambiguously understand, in thermodynamic terms, any inherent differences in the way these important polyanions interact with chiral nanoscale objects.…”
Section: Figuresupporting
confidence: 93%
See 1 more Smart Citation
“…We have reported that a chiral SAMul lysine ligand array can control polyanion binding . Interestingly, however, when using lysine ligands, chiral recognition of heparin does not always occur—Wang and Rabenstein reported that there was no impact of chirality in their peptide heparin binders, whilst we found that the precise structure of the self‐assembling system determined whether chiral recognition was achieved . In this new study, we wanted to gain a more detailed understanding of the chiral preferences of both heparin and DNA, and unambiguously understand, in thermodynamic terms, any inherent differences in the way these important polyanions interact with chiral nanoscale objects.…”
Section: Figuresupporting
confidence: 93%
“…The difference in binding free energy (Δ G bind ) between the best binder ( ld ) and the worst binder ( dl ) is large, at 5.7 kJ mol −1 . This is significantly larger than the 2.6 kJ mol −1 difference in Δ G bind that we observed previously for related systems with glycine instead of alanine units, suggesting that chiral alanine units help pre‐organise the lysine ligands for enantioselective recognition. More detailed thermodynamic analysis indicates that the difference between DNA binders is primarily a result of different enthalpies of binding (Δ H bind differs by up to 4.5 kJ mol −1 ).…”
Section: Figurementioning
confidence: 99%
“…Communications 8532 www.angewandte.org binders (ll slightly better than dl). Thedifference in binding free energy (DG bind )b etween the best binder (ld)a nd the worst binder (dl)islarge,at5.7 kJ mol À1 .T his is significantly larger than the 2.6 kJ mol À1 difference in DG bind that we observed previously for related systems with glycine instead of alanine units, [19] suggesting that chiral alanine units help pre-organise the lysine ligands for enantioselective recognition. More detailed thermodynamic analysis indicates that the difference between DNAb inders is primarily ar esult of different enthalpies of binding (DH bind differs by up to 4.5 kJ mol À1 ).…”
Section: Angewandte Chemiementioning
confidence: 78%
“…Extending this research further, chiral amino acid modifications were made to a very simple amphiphile (C 16 -Lys and C 16 -Gly-Lys). 68 The presence of a glycine spacer unit between Fig. 11 (top) TGD-G2 and (bottom) PAMAM-G2 dendrimers bound to heparin at a charge excess of 0.4 using MD modelling methods.…”
Section: Selectivity In Electrostatic Bindingtowards the Polyanion Worldmentioning
confidence: 99%